All-optical Kerr Polarization Controller - Moroney, N.; Del Bino, L.; Zhang, S.; Woodley, M. T.M.; Hill, L.; Wildi, T.; Wittwer, V. J.; Südmeyer, T.; Oppo, G. L.; Vanner, M.; Brasch, V.; Herr, T.; et al. (Optics InfoBase Conference Papers, 2022)
We demonstrate an all-optical polarization controller in a high-finesse Fabry-Pérot microresonator. Kerr-nonlinearity-induced symmetry breaking splits linear polarized input light into left- and right-circular polarized components, enabling all-optical polarization control with mW-level threshold.
CRIS-Team Scopus Importer:2022-09-09